2022
DOI: 10.1111/gcb.16142
|View full text |Cite
|
Sign up to set email alerts
|

Arctic marine forest distribution models showcase potentially severe habitat losses for cryophilic species under climate change

Abstract: The Arctic is among the fastest-warming areas of the globe. Understanding the impact of climate change on foundational Arctic marine species is needed to provide insight on ecological resilience at high latitudes. Marine forests, the underwater seascapes formed by seaweeds, are predicted to expand their ranges further north in the Arctic in a warmer climate. Here, we investigated whether northern habitat gains will compensate for losses at the southern range edge by modelling marine forest distributions accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…This scenario is imaginable since L. hyperborea and L. digitata and their arctic congener Laminaria solidungula, the CSP of which is unknown, could expand their ranges poleward, potentially mitigating or overcompensating the loss of trailing edge populations. If, however, there is little to no novel arctic habitat for boreal and arctic kelps to expand into (Bringloe et al, 2022), then their global range will contract and their potential contribution to carbon sequestration diminish, mirroring the local processes we predict. This scenario is arguably more likely due to decreased salinity and increased turbidity through glacial and permafrost melt in combination with coastal erosion, and photoperiod-mediated disruption of growth and reproductive cycles in taxa adapted to lower latitudes (Bringloe et al, 2022;Martins et al, 2022).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This scenario is imaginable since L. hyperborea and L. digitata and their arctic congener Laminaria solidungula, the CSP of which is unknown, could expand their ranges poleward, potentially mitigating or overcompensating the loss of trailing edge populations. If, however, there is little to no novel arctic habitat for boreal and arctic kelps to expand into (Bringloe et al, 2022), then their global range will contract and their potential contribution to carbon sequestration diminish, mirroring the local processes we predict. This scenario is arguably more likely due to decreased salinity and increased turbidity through glacial and permafrost melt in combination with coastal erosion, and photoperiod-mediated disruption of growth and reproductive cycles in taxa adapted to lower latitudes (Bringloe et al, 2022;Martins et al, 2022).…”
Section: Discussionmentioning
confidence: 90%
“…If, however, there is little to no novel arctic habitat for boreal and arctic kelps to expand into (Bringloe et al, 2022), then their global range will contract and their potential contribution to carbon sequestration diminish, mirroring the local processes we predict. This scenario is arguably more likely due to decreased salinity and increased turbidity through glacial and permafrost melt in combination with coastal erosion, and photoperiod-mediated disruption of growth and reproductive cycles in taxa adapted to lower latitudes (Bringloe et al, 2022;Martins et al, 2022). We nevertheless emphasise that our predictions of declining CSP beyond the local scale represent a thought experiment, intended to stimulate further study and debate rather than provide firm predictions, being based as they are on finite empirical data.…”
Section: Discussionmentioning
confidence: 90%
“…Modelling efforts to predict the impact of potential warming and acidification scenarios by 2100 on demersal fish showed that habitat loss would be small (0 to 11%), with no appreciable difference between losses for Arctic and Arctic-boreal species (Renaud et al, 2019). The extent of marine forests (macrophytobenthos) within the Arctic basin is also predicted to remain stable (Bringloe et al, 2022), if not increase due to the changing climate (Krause-Jensen et al, 2020). The depth structure of these forests however is likely to shift to shallower waters (Bartsch et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Any patterns regarding functions specifically gained or lost in these populations are purely speculative at the moment; besides needing a more comprehensive formal analysis, the function of many genes will remain biased towards housekeeping genes or otherwise unknown for the time being. Nonetheless, functional differentiation of populations will be an exciting avenue to explore for future work, and potentially highly relevant for predicting climate change responses (Bringloe et al, 2022 ) and informing global kelp/marine forest restoration strategies (Coleman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Global analyses highlight wide variability in kelp ecosystem trends, with local‐scale variation exceeding a small global average decline in abundances (Krumhansl et al, 2016 ). Polar regions may experience expansion of some kelp species as sea‐ice retreat opens new habitat (Bringloe et al, 2022 ; Krause‐Jensen et al, 2020 ), while in other regions, warming threatens to extirpate cold‐adapted flora in favour of warm‐adapted turf‐forming species, with accompanying changes to ecosystem function (Filbee‐Dexter & Wernberg, 2019 ; Filbee‐Dexter et al, 2020 ; Pessarrodona et al, 2021 ; Vergés et al, 2016 ). Safeguarding kelp and the accompanying services they provide will require genomic insights to unravel details about past evolution, the historical environmental processes that underpin current biogeographical patterns, dispersal and exchange of genomic information among populations, and ultimately the capacity for genetic adaptation of populations in a changing climate.…”
Section: Introductionmentioning
confidence: 99%